2012
DOI: 10.1021/ol303065k
|View full text |Cite
|
Sign up to set email alerts
|

“Unclosed Cryptands”: A Point of Departure for Developing Potent Neutral Anion Receptors

Abstract: Six macrocyclic lariat-type compounds, representing a new class of anion receptors, were synthesized in a simple approach. We identified the optimal macroring size and the position of the hydrogen bond donating center in the lariat arm offering the best affinities toward chloride and carboxylate anions. The anion-binding properties of such systems were investigated by applying (1)H NMR titrations in DMSO/water and methanol/DMSO mixtures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 49 publications
1
52
0
Order By: Relevance
“…Unclosed cryptands Uc1-Uc5 [30][31][32] are structurally related to previously mentioned macrocycles M1-M13, however, only one side contains meso diacid moiety (dipicolinic acid), while the other side is constructed here from diacid derived from 2,6-dihydroxyaniline. The nitrogen atom of the latter group is a part of amide equipped with an additional p-nitrophenyl substituent (lariat arm) which is introduced at the intraannular position of the macroring.…”
Section: Unclosed Cryptands (Group Iii)mentioning
confidence: 99%
“…Unclosed cryptands Uc1-Uc5 [30][31][32] are structurally related to previously mentioned macrocycles M1-M13, however, only one side contains meso diacid moiety (dipicolinic acid), while the other side is constructed here from diacid derived from 2,6-dihydroxyaniline. The nitrogen atom of the latter group is a part of amide equipped with an additional p-nitrophenyl substituent (lariat arm) which is introduced at the intraannular position of the macroring.…”
Section: Unclosed Cryptands (Group Iii)mentioning
confidence: 99%
“…There are several types of hydrogen‐bonding building blocks that contain (benzo)pyrrole, urea, and amide units . Owing to their relatively high anion affinity, bisamide building blocks constructed of aromatic skeletons are particularly attractive, as they are readily incorporated into more complex macrocyclic, cryptand, and polycyclic structures ,. Such receptors tend to have exceptionally high affinities for anions and are promising structures in selective anion binding.…”
Section: Introductionmentioning
confidence: 99%
“…It was, however, identified that achiral molecules, particularly macrocyclic structures, may occur as homochiral species in a crystalline form . In recent decades, we demonstrated array of cyclic systems, mainly based on a concept of unclosed cryptands (specific lariat molecules), with various pending arms that affect features of cyclic scaffolds . It turned out that some of these proved to be chiral in a solid state, upon crystallization from a solution.…”
Section: Introductionmentioning
confidence: 99%
“…decades, we demonstrated array of cyclic systems, mainly based on a concept of unclosed cryptands (specific lariat molecules), with various pending arms that affect features of cyclic scaffolds. [36][37][38][39][40][41] It turned out that some of these proved to be chiral in a solid state, upon crystallization from a solution. Secondly, crystals of macrocyclic imines with broken symmetry were recently obtained, exhibiting outstanding enantiomeric excess, with respect to the single crystal.…”
Section: Introductionmentioning
confidence: 99%